Population genetic structure in medicinal plant Lallemantia iberica (Lamiaceae) - FAHIMEH KOOHDAR; MASOUD SHEIDAI; SEYYED MEHDI TALEBI; ZAHRA NOORMOHAMMADI (Biodiversitas Journal of Biological Diversity, 2015)
Koohdar F, Sheidai M, Talebi SM, Noormohammadi Z. 2015. Population genetic structure in medicinal plant Lallemantia iberica (Lamiaceae). Biodiversitas 16: 139-144. Lallemantia iberica (Bieb.) Fischer and C.A. Meyer (sin. Dracocephalum ibericumM.Bieb.) also named Dragon's headâ€ is an annual plant cultivated for its seeds that contain about 30% -38% drying oil (siccative oil). Itsseed oil is used in foods, dye and varnish industry. L. iberica seeds have traditional uses as reconstitute, stimulant, diuretic andexpectorant. L. iberica in an important medicinal plant in our country and grows in various regions with different environmentalconditions. At present no investigation has been reported about population genetic structure of this valuable plant species in Iran.Therefore, we carried out population genetic analysis of 11 populations of L. iberica by using ISSR molecular markers for the first time.Genetic diversity analysis revealed high within population genetic variability. AMOVA test produced significant genetic differenceamong the studied populations. Mantel test revealed significant correlation between genetic distance and geographical distance of thepopulations. STRUCTURE analysis and K-Means clustering revealed population genetic fragmentation and the presence of three genepools for this species. The assignment test revealed the occurrence of limited gene flow among the populations. The results suggestedthat genetic divergence, limited gene flow, genetic drift and local adaptation have played role in diversification of L. iberica. Key words: Gene flow, population fragmentation, IBD, Lallemantia iberica.